Perception of puerperal women on the use of non-pharmacological methods for pain relief in childbirth work (Research, Society and Development, 2021)
Objective: To describe the perception of puerperal women about the use of non-pharmacological methods for pain relief during labor and delivery. Methodology: This is a descriptive study with a qualitative approach, carried out in a Public Maternity Hospital in the city of Recife - PE. 10 puerperal women who used non-pharmacological methods of pain relief during labor and delivery were interviewed. The data were produced through semi-structured interviews and analyzed according to the content analysis technique proposed by Bardin. Results: From the analysis of the speeches of the participants, four thematic categories emerged: knowledge about non-pharmacological methods, a sense of well-being and pain relief, reduction in labor time and appreciation of the companion. Conclusion: The use of non-pharmacological methods of pain relief had positive effects contributing to the experience of labor and delivery. The importance of encouraging women's autonomy from prenatal care in primary care is highlighted, as well as having a welcoming and trained team, which provides the necessary information and guidance, contributing to the safety of the woman and her companion.